PReventing Idiopathic SCOliosis PROgression (PRISCOPRO): A protocol for a quadruple-blinded, randomized controlled trial comparing 3D designed Boston brace to standard Boston brace. - Elias Diarbakerli; Anastasios Charalampidis; Allan Abbott; Paul Gerdhem (PLoS ONE)
Introduction Idiopathic scoliosis is the most common spinal deformity in children. Treatment strategies aim to halt progression of the curve. Patients are treated mainly with thoracolumbosacral orthosis (TLSO) if indicated. This form of brace treatment has been shown to be cumbersome and tough on growing individuals. However, computer aided design and manufactured (CAD/CAM) braces might increase comfortability and ultimately outcome if compliance is improved. In a multicenter, randomized controlled trial, we aim to compare CAD/CAM designed Boston 3D-brace to standard Boston brace. Methods Subjects: 170 previously untreated and skeletally immature children diagnosed with idiopathic scoliosis, aged 9-17 years of age (curve magnitude Cobb 25-40 degrees) will be included. Interventions: Both groups will receive a physical activity prescription according to the World Health Organization recommendations. Randomization will be performed 1:1 to a 3D CAD/CAM designed Boston 3D-brace or a standard Boston brace, both with prescribed daily wear time of 20 hours. Outcome: The subjects will participate in the study until curve progression or until skeletal maturity. The primary outcome variable is failure of treatment, defined as progression of the Cobb angle more than 6 degrees compared to the baseline x-ray. The progression is confirmed if seen on two consecutive standing spinal x-rays. Radiographs will be taken at each six-month follow-up. Secondary outcome measures include patient and clinical reported outcomes, including number of individuals requiring surgical intervention. Discussion This study will show if efficacy in brace treatment can be improved with new brace designs. Trial registration The protocol has been registered on ClinicalTrials.gov, identifier: NCT04805437.